1991
DOI: 10.1172/jci115214
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mimicry in Candida albicans. Role of an integrin analogue in adhesion of the yeast to human endothelium.

Abstract: Hematogenous infection with the yeast Candida albicans now occurs with increasing frequency in the neonate, the immunocompromised patient, and the hyperglycemic or hyperalimented host. Yeast-phase C. albicans expresses a protein that is antigenically and structurally related to CD11b/CD18, a member of the 2 integrins and a well-characterized adhesin for mammalian neutrophils. Both the neutrophil protein and its analogue in C. albicans have an identical affinity for the C3 ligand iC3b, and both proteins are sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 38 publications
(22 reference statements)
3
89
0
Order By: Relevance
“…The iC3b binding protein(s) discussed below contributed to adherence to umbilical vein endothelium. Two monoclonal antibodies that recognize human integrin subunit tm partially inhibited adherence (Gustafson et al, 1991).…”
Section: Removalmentioning
confidence: 97%
See 3 more Smart Citations
“…The iC3b binding protein(s) discussed below contributed to adherence to umbilical vein endothelium. Two monoclonal antibodies that recognize human integrin subunit tm partially inhibited adherence (Gustafson et al, 1991).…”
Section: Removalmentioning
confidence: 97%
“…(3) In vitro growth conditions of the fungus-such as temperature (Lee and King, 1983), medium composition (Alloush et al, 1996;Yan et al, 1998b), carbon source (McCourtie and Douglas, 1985;Gustafson et al, 1991), or the presence of a specific inducer (Yan et al, 1998a)-may alter the expression of an adhesin.…”
Section: Removalmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these proteins, receptors for complement factors (Calderone et al, 1988;Gustafson et al, 1991;Alaei et al, 1993), as well as for fibrinogen (Bouali et al, 1987;Martinez et al, 1994), fibronectin (Kalon et al, 1988;Klotz & Smith, 1991 ;Klotz et al, 1994), laminin (Bouchara et al, 1990;Lopez-Ribot et al, 1994) and other extracellular matrix genes encoding these proteins, the presence of these proteins on the cell surface was investigated and it was concluded that these and probably other cytosolic proteins can be bound to cell walls in vitro, as can happen in vivo. Their presence in the C. albicans cell wall seems to be a consequence of cell lysis and not a result of a secretory process.…”
Section: Introductionmentioning
confidence: 99%